The Authority of Adat Institutions in Resolving Marital Disputes in Aceh: A Legal Review - Zubir Zubir; Alimuddin Alimuddin (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
Aceh’s legal framework is distinctive due to the coexistence of state law, Islamic law, and adat (customary) law, particularly in handling marital disputes. Adat institutions hold a significant role within local communities, as they provide culturally grounded mechanisms for resolving conflicts, often emphasizing restorative justice and social harmony. However, the precise legal authority of these institutions remains complex, especially when their jurisdiction overlaps or conflicts with formal judicial bodies such as the Mahkamah Syar’iyah. This study aims to critically review the legal basis and scope of authority of adat institutions in resolving marital disputes in Aceh within the context of Indonesian law. Utilizing a normative legal research method combined with conceptual and statutory analyses, this research examines relevant legislation, including Law No. 11 of 2006 on the Governance of Aceh and Law No. 23 of 2004 on the Elimination of Domestic Violence. Additionally, it draws on doctrinal sources and practical adat dispute resolution cases in Aceh. The findings demonstrate that adat institutions remain trusted mediators that prioritize reconciliation and community consensus in marital conflicts. Nonetheless, their authority is not absolute and is limited by national legal frameworks, especially concerning divorce proceedings, child custody, and cases of domestic violence, which fall under the jurisdiction of Islamic courts. This overlapping jurisdiction can lead to legal ambiguities and inconsistent outcomes. The study contributes valuable insights for policymakers and legal practitioners seeking to enhance coordination and integration between adat dispute resolution mechanisms and formal legal systems. Strengthening regulatory clarity and fostering collaboration can support more effective dispute resolution that respects Acehnese cultural traditions while aligning with national legal standards.